2021
DOI: 10.1002/art.41652
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐Resident Memory CD8+ T Cells From Skin Differentiate Psoriatic Arthritis From Psoriasis

Abstract: Objective To compare immune cell phenotype and function in psoriatic arthritis (PsA) versus psoriasis in order to better understand the pathogenesis of PsA. Methods In‐depth immunophenotyping of different T cell and dendritic cell subsets was performed in patients with PsA, psoriasis, or axial spondyloarthritis and healthy controls. Subsequently, we analyzed cells from peripheral blood, synovial fluid (SF), and skin biopsy specimens using flow cytometry, along with high‐throughput transcriptome analyses and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 52 publications
1
30
1
1
Order By: Relevance
“…While, to our knowledge, the role of dnTs and HSPCs in PSA has not been extensively investigated, dnT cells have been reported to infiltrate psoriatic skin as well as participate in IL-23/IL-17 signaling in mouse models of psoriasis ( 34 ) and spondyloarthritis ( 35 ), and the proliferation and differentiation of HSPCs is currently known to respond to systemic interferon and TNF signaling ( 36 ). While we observed increased peripheral Tregs in PSA patients, whether this subset is generally increased or decreased in PSA is still unclear in light of conflicting results found in other studies ( 37 , 38 ).…”
Section: Discussioncontrasting
confidence: 69%
“…While, to our knowledge, the role of dnTs and HSPCs in PSA has not been extensively investigated, dnT cells have been reported to infiltrate psoriatic skin as well as participate in IL-23/IL-17 signaling in mouse models of psoriasis ( 34 ) and spondyloarthritis ( 35 ), and the proliferation and differentiation of HSPCs is currently known to respond to systemic interferon and TNF signaling ( 36 ). While we observed increased peripheral Tregs in PSA patients, whether this subset is generally increased or decreased in PSA is still unclear in light of conflicting results found in other studies ( 37 , 38 ).…”
Section: Discussioncontrasting
confidence: 69%
“…Of interest is the comparison between skin of PsO and PsA patients, which is informative to understand the relation between the two diseases. These kinds of studies are unfortunately scarce (53,54), but crosssectional comparisons do point to molecular differences between skin of PsO and PsA patients (54).…”
Section: Initiation Of Psoriatic Arthritismentioning
confidence: 99%
“…CD8+ T cells are polyfunctional enabling the production of a wide range of cytokines both in skin and joints (66). In blood of PsA patients, more memory CD8+ T cells have been found compared to healthy controls and PsO patients (53), underlining a possible important role of memory CD8+ T cells in PsA. Also in synovial fluid of PsA patients, these CD8+ cells are abundantly present and are clonally expanded more extensively than CD4+ T cells (66,71).…”
Section: From Psoriasis To Psoriatic Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…An early study of skin from PsA patients (n = 15) vs. Pso patients (n = 5) and normal control skin (n = 4) identified increased numbers of CD45Ro T-cells, greater vascularity, the presence of B-cells, and increased numbers of DR +epidermal cells as markers for arthritis in patients with Pso (34). While these findings have not been replicated, a more recent study by Leijten et al identified CCR10+ CD8+ T cells as being enriched in PsA peripheral blood (35). CCR10+ CD8+ T cells were detected under inflammatory and homeostatic conditions in Pso skin but were not enriched in synovial fluid.…”
Section: Cellular and Tissue Markers Of Psa In Patients With Psomentioning
confidence: 99%